2017
DOI: 10.2147/tcrm.s142193
|View full text |Cite
|
Sign up to set email alerts
|

<em>Helicobacter pylori </em>infection and severity of coronary atherosclerosis in patients with chronic coronary artery disease

Abstract: AimControversy exists concerning the relation between Helicobacter pylori (HP) infection and coronary artery disease (CAD). We aimed to examine the relationship between HP infection and severity of coronary atherosclerosis in patients with chronic CAD.Patients and methodsA total of 150 patients (109 [73%] men; mean age 62.61±10.23 years) scheduled for coronary artery bypass grafting surgery were consecutively enrolled in the cross-sectional study. According to rapid urease test and/or gastric biopsy samples st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Jukic et al studied the correlation between H. pylori positivity, determined by histology and CLO test, and the results of coronary angiograms in patients scheduled for coronary artery bypass grafting surgery. 5 They found no association in the severity of the vessel atherosclerosis score, the Gensini score, and the angiographic severity score between H. pylori-positive and negative patients, but a significant correlation between arterial hypertension and H. pylori Moreover, H. pylori-negative patients showed a better unified PD rating scale (UPDRS-III) compared to H. pylori-positive patients and the score significantly improved after H. spylori eradication. 13 On the other hand, Liu et al performed a cohort study involving 94 patients with idiopathic PD who were screened for H. pylori infection and were divided into different groups based on H. pylori positivity and successful H. pylori eradication.…”
Section: R E V I E W a R T I C L Ementioning
confidence: 94%
See 1 more Smart Citation
“…Jukic et al studied the correlation between H. pylori positivity, determined by histology and CLO test, and the results of coronary angiograms in patients scheduled for coronary artery bypass grafting surgery. 5 They found no association in the severity of the vessel atherosclerosis score, the Gensini score, and the angiographic severity score between H. pylori-positive and negative patients, but a significant correlation between arterial hypertension and H. pylori Moreover, H. pylori-negative patients showed a better unified PD rating scale (UPDRS-III) compared to H. pylori-positive patients and the score significantly improved after H. spylori eradication. 13 On the other hand, Liu et al performed a cohort study involving 94 patients with idiopathic PD who were screened for H. pylori infection and were divided into different groups based on H. pylori positivity and successful H. pylori eradication.…”
Section: R E V I E W a R T I C L Ementioning
confidence: 94%
“…We also reported a significantly higher occurrence of major adverse cardiovascular event rates (MACE) in CagA‐positive patients compared to CagA‐negative patients (HR: 2.25; 95% CI: 1.34, 2.95; P = 0.01), which was also confirmed with Cox multivariate analysis (HR: 2.33; 95% CI: 1.30, 3.14; P = 0.01). Jukic et al studied the correlation between H. pylori positivity, determined by histology and CLO test, and the results of coronary angiograms in patients scheduled for coronary artery bypass grafting surgery . They found no association in the severity of the vessel atherosclerosis score, the Gensini score, and the angiographic severity score between H. pylori ‐positive and negative patients, but a significant correlation between arterial hypertension and H. pylori infection ( P = 0.014).…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…While it is widely known that Helicobacter pylori (H. pylori) may cause gastritis, gastric ulcer, gastric cancer, gastric lymphoma, 1 idiopathic thrombocytopenic purpura, 2 and iron-deficiency anemia, 2 this infection may also be involved in non-digestive tract diseases such as chronic urticaria, 3 Alzheimer's disease, 4 Parkinson's disease, 5 atrial fibrillation, 6 liver diseases, 7 Behçet's disease, 8 hyperemesis gravidarum, 9 infertility, 10 glaucoma, 11 alopecia areata, 12 and arteriosclerosis disease 13 including dyslipidemia, 14,15 diabetes, [16][17][18] obesity, 19,20 hypertension, 15,[21][22][23] chronic kidney disease 24 and cardiovascular disease. [24][25][26][27][28][29] Several reports have indicated a relationship between H. pylori and acute coronary syndrome, 25 which suggests that H. pylori infection is a risk factor for cardiovascular disease (CVD); 24,26,27 moreover, patients with H. pylori infection show an approximately 3-times higher risk of coronary artery disease than do healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Associations of H. pylori infection with hypercholesterolemia, 14 low levels of high-density lipoprotein-cholesterol (HDL-C), and high levels of low-density lipoprotein-cholesterol (LDL-C) have been reported. 15 Several studies have found that H. pylori is associated with insulin resistance 16 and diabetes mellitus. 17,18 Furthermore, H. pylori infection has been reported to be positively correlated with body mass index (BMI).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation